Reduction of cryopreservation-induced structural, functional and molecular damages in ram sperm by hydrated C60 fullerene - Gungor, Ibrahim Halil; Turk, Gaffari; Cinkara, Serap Dayan; Acisu, Tutku Can; Tektemur, Ahmet; Yeni, Deniz; Yuce, Abdurrauf (Wiley, 2024)
This study aimed to investigate the morphological, functional and molecular changes in frozen-thawed ram sperm using an extender containing different concentrations of hydrated carbon 60 fullerene (C(60)HyFn), a nanotechnological product. Semen taken from each of the seven Akkaraman rams were pooled. Semen collection was done twice a week and it continued for 3 weeks. Each pooled semen sample was divided into six equal groups and diluted with tris + egg yolk extender including 0 (control), 200, 400, 800 nM, 1 and 5 mu M concentrations of C(60)HyFn at 37 degrees C. They were then frozen in liquid nitrogen vapour at -140 degrees C, stored in liquid nitrogen container (-196 degrees C) and thawed at 37 degrees C for 25 s before analysis. In comparison with control, C(60)HyFn addition prior to freezing procedure provided significant increases in total and progressive motility rates, glutathione peroxidase, catalase activities and percentage of highly active mitochondria, and significant decreases in dead and abnormal sperm rates, lipid peroxidation, caspase-3 and DNA fragmentation levels in frozen-thawed ram semen. When compared to control, C(60)HyFn supplementation significantly down-regulated the expression levels of miR-200a and KCNJ11, and significantly up-regulated the expression levels of miR-3958-3p (at the concentrations of 200, 400, 800 nM and 1 mu M), CatSper1 (at the concentrations of 200, 400 nM and 5 mu M), CatSper2 (at the concentrations of 1 and 5 mu M), CatSper3 (at the concentrations of 200, 400 nM, 1 and 5 mu M), CatSper4 (at all concentrations), ANO1 (at the concentrations of 800 nM, 1 and 5 mu M) and TRPV5 (at the concentrations of 200, 400 and 800 nM). The addition of C(60)HyFn had no effect on global DNA methylation rates. As a result, C(60)HyFn supplementation to ram semen extenders may be beneficial in reducing some of the functional, structural and molecular damages in sperm induced by the freeze-thawing procedure.
Keywords: hydrated carbon 60 fullerene; ion channels; miRNA; ram; semen